The Effect of Caffeine Supplementation in Egg-Yolk Tris Extender on Motility and Velocity of Garut Sheep Sperm Separation - Rasad, SD; Soeparna, Soeparna; Nurfaidah, L (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
The aims of this research were to know the effect of caffeine in Tris egg yolk extender on motility and velocity of Garut Ram sperm after separation and to find out the optimum dosage of caffeine for both parameters. This research used experimental design with Completely Randomized Design (CRD) with four treatments on different dosage (0 mM, 2 mM, 4 mM and 6 mM), each treatment is repeated five times. The result showed that the supplemtation of caffeine significantly influence sperm motility of Garut Ram sperm after separation. The highest sperm motility was on dosage 4 mM that was 63.57% on top fraction and 65.90% on below fraction. The highest sperm velocity was on dosage 4 mM that was 62.37 µm/second on top fraction and 64.24 µm/second on below fraction and significantly influence sperm velocity. The conclusion, 4 mM dosage of caffeine was the optimum dosage to reach the highest motility and velocity of Garut Ram sperm both on top and below fractions. (Animal Production 12(3): 139-143 (2010)Key Words: spermatozoa, Garut ram, sperm separation, caffeine